Hierarchically porous carbon architectures embedded with hollow nanocapsules for high-performance lithium storage1. Issue 9 (7th March 2015) - Yu, Chang; Chen, Meng; Li, Xiaoju; Zhao, Changtai; He, Lianlong; Qiu, Jieshan
<x xml:space="preserve">Abstract</x> Hierarchically porous carbon architectures composed of a micro-sized porous carbon sphere matrix embedded with hollow nanocapsules are configured, demonstrating a large capacity and an ultra-high rate capability in lithium ion batteries.